Corbin, H. La Paradoja del Monoteísmo - Bezerra, Cicero Cunha (Princípios: Revista de Filosofia (UFRN), 2010)
Resenha do livro de: CORBIN, H. La paradoja del monoteismo. Trad. Maria Tabuyo y Agustin Lopez. Madrid: Losada, 2003.289 paginas,